SAMARQAND VILOYATI JANUBIY HUDUDLARIDA CITELLUS FULVUS POPULYATSIYASINING BIOEKOLOGIK TAVSIFI - Umarov M.N., Umarov M.N. (Actual problems and prospects of the study of the fauna, 2024)
The article analyzes the bioecological description of the population of Citellus fulvus, a representative of the widespread rodentia family, in the territory of Urgut district of Samarkand region. The distribution of this species in the territory of Urgut district of Samarkand region is revealed. The composition of Citellus fulvus colonies, differentiation by age, structure of nests, differentiation of morphological signs by age and region were analyzed.